Peran Komunikasi Politik Pemangku Kepentingan Pada Pelaksanaan Kebijakan Perberasan - M.S. Nasution; A.V.S. Hubeis; A. Saleh (Jurnal Komunikasi Pembangunan, 2008)
Rice in Indonesia has a strategic role especially in economic. Rice issues also playing a sensitive role on social andpolitical security. Rice is also a prime food for the majority of Indonesian people; therefore need a good and rightmanagement from upper course up to lower course. The strong role of political communication become one of theway on the making of rice policy implementation especially by involving those interest functionary on rice. Thisresearch was designed as survey with descriptive correlation, respondent comprised of farmer organization,government, rice entrepreneur, and IV commission of house of representative. Quantitative analysis used bydescriptive statistical and correlation analysis with rank Spearman correlation statistical test. The role of politicalcommunication of farmer organization are on the middle category, government on strong category, rice entrepreneuron middle category and IV commission of House of Representative on middle category. At the personal characteristicof farmer organization on formal education, experiences on farmer organization and IV commission of house ofrepresentative actually significant with the role of political communication on rice policy implementation. At thesituational characteristic on communication access of government and IV commission of house of representative,political participation of all interest functionary are tangibly significant and only IV commission of house ofrepresentative political perception that tangible not significant with the role of political communication on rice policyimplementation. At political communication behavior, the information dependency on mass media on governmenttangible significant. Meanwhile respons on public opinion for IV commission of house of representative is significantand political attitude all of interest functionary tangible significant with the role of political communication of ricepolicy implementation.Mass media has their role as one of the information source which is considerably objectiveand public opinion on the subject of rice policy implementation has also considerably become one of intakecorrection. The choices of Political attitude at the current time are valuable to bring out cooperation and re-actualizestrong and powerful policy implementation in the future.